The efficacy of mindfulness-based therapy for anxiety, social skills, and aggressive behaviors in children and young people with Autism Spectrum Disorder: A systematic review - Loftus, Tundi; Mathersul, Danielle C.; Ooi, Michelle; Yau, Shu H. (Frontiers in Psychiatry, 2023)
The purpose of this systematic review was to examine the efficacy of mindfulness-based interventions for improving anxiety, social skills, and aggressive behaviors in children and young people (CYP) with Autism Spectrum Disorder (ASD); summarise the results across clinic, home, and school contexts; and evaluate the quality of these interventions for clinical practice. A search of the PsycINFO, Medline (Ovid), Web of Science, and Scopus databases was conducted in June 2021, and no date restrictions were applied. Inclusion criteria were quantitative or qualitative research implementing a mindfulness-based intervention for CYP aged 6 to 25 years with a diagnosis of ASD, Pervasive Development Disorder, or Asperger’s Syndrome. We identified 23 articles for inclusion including within subject pre- and post-testing, multiple baselines, and randomised control trials, among other research designs. Of these, a quality analysis conducted using an ASD research-specific risk of bias tool found over half (14) were of weak methodological quality, whereas only four and five were found to be of strong and adequate quality, respectively. While the results of this systematic review suggest promising evidence for the use of mindfulness-based interventions to improve anxiety, social skills, and aggressive behaviors in CYP with ASD, results should be interpreted with caution due to the limitations resulting from the overall weak quality of the studies.